PENERAPAN PENDEKATAN DELIKAN, DAN CTL UNTUK MENINGKATKAN PRESTASI BELAJAR PKN MAHASISWA UNDERACHIEVER - Juarsa, Osa; Badeni, Badeni (Jurnal PGSD, 2019)
The purpose of this research is to (a) determine the factors that cause students to be underachiever; (b) determine factors that cause students are not embedded character of value learned; (c) know character planting and improvement strategies of underachiever students learning achievement to the extent that they should achieve through hear, see and do (HSD) approach, structure knowledge and CTL. Action research approach was conducted in research. There are two results of this study. Fistly the lack of caring and understanding to students and the lack of lecturers and parents knowledge on how to guide, care and let students learn addressing the root causes of student to be underachiever. Secondly, learning achievement and character values of the subject will be more improved and internalized into the underachiever students if the HSD,  and CTL approach is integrated applicated.